A clínica do desenraizamento: atendimento a crianças em situação de risco - Guimarães, Giselle Faria (2007)
In this work I reflect about the possibilities of intervention on the care with children in risk situation, considering the importance of the environment and the relationship with the other in order for them to establish a creative relationship with the world in which they live. My interest came from my experience at Project Quixote, presented at the beginning of this text. I also present stories of children that passed through the Project, seeking to understand the suffering they show us. This suffering, that many times comes as violent behaviors, learning problems, drug abuse among other, cannot be reduced to its psychic or social aspect, but must be understood on its ontological aspect since it is about experiences that fracture the human ethos. They are children who suffer because they live in a world more inhospitable at each day, in which they can t find the conditions that allow their humanity to happen. The children we meet are marked, in different degrees, by the disenchantment and lack of hope. We suffer the consequences of a rootlessness process more intense at each day. In this way, I used the contributions of D.W. Winnicott, who highlights the importance of the relationship with the other and the necessary conditions the environment must offer so that the human being can constitute itself, and the elaborations of Simone Weil about the notion of rooting and rootlessness. Also fundamental were Safra s reflections on the suffering as a consequence of ethical fractures. The interventions must be guided by the place issue, by the need to offer a place in the human world given by the relationship that establishes between the children and the professional, the team and the institution that take care of her. It is from the experience of having a place related to self that the child will be able to live or relive the enchantment experience